Pengaruh Advertorial mengenai CSR dalam Pembentukan Citra Merek - Intan Primadini (Ultimacomm: Jurnal Ilmu Komunikasi, 2016)
This research aims to examine the influence of the advertorial credibility level toward public perception on advertorial. The advertorial selected for this research is Lifebuoy’s corporate social responsibility program. The study seeks to assess the influence of public perception on the CSR in Lifebuoy brand image and to identify the different perception between Lifebuoy users and non-users on its CSR and brand image. The study uses a positivist paradigm with explanative approach. Data were obtained through survey using questionnaires. The population of this research were students of the extension program of the Faculty of Social and Political Science, Universitas Indonesia. Sixty samples were elected through random sampling method. It can be concluded that the advertorial credibility rate has a significant influence on the public perception of CSR, while CSR also brings a significant influence on the Lifebuoy brand image. However, there is no significant difference between perception of the Lifebuoy users and non-users concerning CSR and brand image. Keywords: Advertorial, brand image, corporate social responsibility, Lifebuoy, marketing public relations